Transjugular intrahepatic Porto-systemic shunt positively influences the composition and metabolic functions of the gut microbiota in cirrhotic patients. Issue 5 (May 2023) - Gitto, Stefano; Vizzutti, Francesco; Baldi, Simone; Campani, Claudia; Navari, Nadia; Falcini, Margherita; Venturi, Giulia; Montanari, Stanislao; Roccarina, Davide; Arena, Umberto; Pallecchi, Marco; Di Bonaventura, Chiara; et al.
Abstract: Background & aims: Cirrhosis and its complications may affect gut microbiota (GM) composition. Transjugular intrahepatic portosystemic shunt (TIPS) represents the most effective treatment for portal hypertension (PH). We aimed to evaluate whether TIPS placement modifies GM composition and metabolic function. Methods: A compositional and functional GM analysis was prospectively performed in 13 cirrhotic patients receiving TIPS. Patients receiving systemic or non-absorbable antibiotics for any indications were excluded. Fecal samples were collected before and three months after TIPS. GM was analyzed by 16S ribosomal RNA sequencing. Small- and medium-chain fatty acids (SCFAs and MCFAs, respectively) were measured by gas chromatography/mass spectrometry. Results: TIPS placement resulted in a mean 48% reduction in portal-caval pressure gradient. No recurrence of PH related complications was observed. After TIPS, increased levels of Flavonifractor spp. ( p  = 0.049), and decreased levels of Clostridiaceae ( p  = 0.024), these latter linked to abdominal infections in cirrhotic patients, were observed. No differences were found in the SCFAs signature while analysis of MCFA profiles showed a decreased abundance of pro-inflammatory isohexanoic ( p <0.01), 2-ethylhexanoic ( p <0.01) and octanoic acids ( p <0.01) after TIPS. Conclusion: Correction of PH following TIPS results in modifications of GM composition which could be potentially beneficial and reduces the levels of fecal pro-inflammatory MCFAs.